Pendapatan dalam Penggunaan Alokasi Waktu Tenaga Kerja Keluarga: Studi Kasus Peternak Sapi Bali di Sentra Pengembangan Sulawesi Tenggara, Indonesia: Pendapatan dan Alokasi Waktu Curahan Tenaga Kerja Keluarga pada Usaha Ternak Sapi Bali di Sulawesi Tenggara, Indonesia - Wiwiek Rindayati; Dominicus Savio Priyarsono; Gerhana Gerhana; La Ode Nafiu; Musram Abadi (Universitas Andalas, 2026)
Income from Bali cattle husbandry with family labor time allocation become highly relevant, as work time efficiency can contributed to increased productivity and farmers' income in the region. The aim of this research is to analyze the income obtained by farmers based on the allocation of work time used in Bali cattle husbandry. The study was conducted in Konawe Selatan Regency and Muna Regency, Southeast Sulawesi, as centers for Bali cattle development. Data were collected from June to October 2024 through questionnaires, interviews with 240 Bali cattle farmers, field surveys, and Focus Group Discussions (FGD). Income analysis was used to examine the income of Bali cattle farmers, while the amount of work time allocation in Bali cattle handling was calculated using the standard measure of man-days, namely MDP (Man-Days Equivalent) or Workdays. The research results show that the allocation of family labor time in Konawe Selatan Regency, amounting to 3.74 MDP, yielded an income of IDR 3,542,383.90, whereas in Muna Regency, a family labor time allocation of 3.73 MDP resulted in an income of IDR 5,437,262.61.